2008
DOI: 10.1158/1055-9965.epi-08-0078
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Cervical Cancer Screening between Asian American and Non-Hispanic White Women

Abstract: Background: Asian American women have higher cervical cancer mortality rates than non-Hispanic White women, yet have lower Pap screening rates than their White counterparts. This study examined whether ethnic differences in the use of Pap screening were associated with differences in cultural views, controlling for demographic and access factors. Methods: Cross-sectional survey data from the Commonwealth 2001 Health Care Quality Survey were used. Non-Hispanic White (n = 2,146) and Asian American women (includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
54
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 18 publications
3
54
0
Order By: Relevance
“…About one half of the participants expressed concerns about not had information and prefer to getting a Pap test, but the majority disagree that money or time act as a barrier, in contrast, these concerns were noted among Vietnamese American women [36]. Also, these factors which have already been reported in other studies [37,38,39,40]. In our study, the most frequently perceived cultural barriers to obtaining Pap tests were being uncomfortable with having a test performed by a male doctor but prefer female doctor (46.9%), disagree not needing a test when feeling well (61.2%), believing a test will be painful or unpleasant (31.7%), and believing a Pap test is embarrassing (30.1%).…”
Section: Discussionmentioning
confidence: 74%
“…About one half of the participants expressed concerns about not had information and prefer to getting a Pap test, but the majority disagree that money or time act as a barrier, in contrast, these concerns were noted among Vietnamese American women [36]. Also, these factors which have already been reported in other studies [37,38,39,40]. In our study, the most frequently perceived cultural barriers to obtaining Pap tests were being uncomfortable with having a test performed by a male doctor but prefer female doctor (46.9%), disagree not needing a test when feeling well (61.2%), believing a test will be painful or unpleasant (31.7%), and believing a Pap test is embarrassing (30.1%).…”
Section: Discussionmentioning
confidence: 74%
“…9 Despite the proven benefits of Pap tests in the early detection of cervical cancer, studies across the United States show that Vietnamese Americans report lower usage of Pap testing than other population subgroups. [10][11][12] Most studies of Vietnamese American women's cervical cancer screening in the 1990s indicated that fewer than 50% of women ever had a Pap test. [13][14][15][16] The screening rates have increased since 2000-due in part to public health efforts to meet the Healthy People 2000 goal-ranging from 55% to 76%.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16] The screening rates have increased since 2000-due in part to public health efforts to meet the Healthy People 2000 goal-ranging from 55% to 76%. 2,[11][12][17][18][19][20][21][22][23][24] However, the screening rates were still far lower than that of the general American population. The Commonwealth 2001 Health Care Quality Survey reported a rate of 55% for obtaining a recent Pap test among Vietnamese American women, lower than the overall rates among Asian American women (70%) and nonHispanic white women in the United States (81%).…”
Section: Introductionmentioning
confidence: 99%
“…69,72 Many women prefer female health care providers to perform screening. [73][74][75][76] In addition, cultural views on screening may affect a woman's willingness to undergo the procedure, 77,78 as might misconceptions regarding Pap testing. [79][80][81] Other factors affecting the willingness to undergo screening include fear, fatalistic attitudes, embarrassment, fear of pain or discomfort, anxiety and stress related to diagnosis, distrust of the health care system and the belief that screening is not necessary without illness.…”
mentioning
confidence: 99%